Seroprevalence of brucellosis in yaks (Poephagus grunniens) in India - Rahman, H; Bhattacharya, M; Rajkhowa, J; Soud, N; Nandankar, U; Mukherjee, S (The Indian Journal of Animal Sciences, 2007)
A study conducted at the National Research Centre on Yak, Arunachal Pradesh, India on the seroprevalence of brucellosis in yaks (Poephagus grunniens) revealed that the overall prevalence of brucellosis in yaks was 16.00%. The prevalence was higher among females (18.18%) compared to male yaks (12.81%). The prevalence of brucellosis was highest in yak cows (22.81%) followed by yak bulls (12.81%) and yak heifers (12.29%). The prevalence of brucellosis was higher (18.82%) among animals reared at a lower altitude (West Kameng district, 2751 masl) than those (10.00%) are reared at higher altitude (Tawang district, 3500 masl). The possible roles of feral fauna and domestic livestock in the transmission of this disease to yaks and vice versa are briefly discussed. Various measures that may help in the prevention and control of brucellosis in yaks are also surveyed. This appears to be first report on the seroprevalence of brucellosis in yaks in India.